Downregulation of hsa_circ_0005243 induces trophoblast cell dysfunction and inflammation via the β-catenin and NF-κB pathways - Huiyan Wang; Wenbo Zhou; Guangtong She; Bin Yu; Lizhou Sun (BMC, 2020)
Abstract Background Gestational diabetes mellitus (GDM) is a common complication in pregnancy that poses a serious threat to the health of both mother and child. While the specific etiology and pathogenesis of this disease are not fully understood, it is thought to arise due to a combination of insulin resistance, inflammation, and genetic factors. Circular RNAs (circRNAs) are a special kind of non-coding RNA that have attracted significant attention in recent years due to their diverse activities, including a potential regulatory role in pregnancy-related diseases, such as GDM. Methods We previously reported the existence of a novel circRNA, hsa_circ_0005243, which was identified by RNA sequencing. In this study, we examined its expression in 20 pregnant women with GDM and 20 normal pregnant controls using quantitative reverse transcription PCR analysis. Subsequent in vitro experiments were conducted following hsa_circ_0005243 knockdown in HTR-8/SVneo cells to examine the role of hsa_circ_0005243 in cell proliferation and migration, as well as the secretion of inflammatory factors such as tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6). Finally, we examined the expression of β-catenin and nuclear factor kappa-B (NF-κB) signaling pathways to assess their role in GDM pathogenesis. Results Expression of hsa_circ_0005243 was significantly reduced in both the placenta and plasma of GDM patients. Knockdown of hsa_circ_0005243 in trophoblast cells significantly suppressed cell proliferation and migration ability. In addition, increased secretion of inflammatory factors (TNF-α and IL-6) was observed after hsa_circ_0005243 depletion. Further analyses showed that knockdown of hsa_circ_0005243 reduced the expression of β-catenin and increased nuclear NF-κB p65 nuclear translocation. Conclusions Downregulation of hsa_circ_0005243 may be associated with the pathogenesis of GDM via the regulation of β-catenin and NF-κB signal pathways, suggesting a new potential therapeutic target for GDM.